O papel dos influenciadores digitais na decisão de compras: uma análise dos aspectos percebidos pelos seguidores - Teixeira, Ligia Rodrigues (Brasil, 2024)
Social networks have become fundamental, shaping consumer behaviors and purchasing decisions. In this context, digital influencers stand out as key figures, using their accounts to connect companies and followers, directly influencing their choices. This research aimed to analyze the aspects that followers consider relevant in the purchase decision based on recommendations of these professionals. It is a qualitative-quantitative approach with data collection being carried out through a questionnaire applied to 250 participants in the city of Manaus. The profile of the respondents is in the age group of 18 to 24 years, with the predominance of the female audience. It was noticed that there is a positive effect on the disclosure made by influencers, since more than half of the participants said they had already purchased products indicated by these professionals. In relation to the branches of products and services that followers are more likely to buy, those of beauty, fashion and gastronomy stood out. Instagram and TikTok were pointed out as the most used social networks by respondents. As for marketing strategies, the most effective are: reviews and unboxings, short stories, "before and after" comparisons and discount coupons. The aspects most valued by followers include the influencer being a source of product news, the influencer's personal experience with products and services, the visual quality of publications and the influencer's credibility. These results highlight the importance of digital influencers as influential agents in the purchase decision process in the digital age and offer valuable insights for companies and marketers who want to optimize their communication and digital marketing strategies.